Long‐term results of combined cardiac contractility modulation and subcutaneous defibrillator therapy in patients with heart failure and reduced ejection fraction - Röger, Susanne; Rudic, Boris; Akın, Ibrahim; Shchetynska-Marinova, Tetyana; Fastenrath, Fabian; Tueluemen, Erol; Liebe, Volker; El-Battrawy, Ibrahim; Baumann, Stefan; Kuschyk, Jürgen; Borggrefe, Martin (Clinical cardiology, 2018)
Background - Cardiac contractility modulation (CCM) is an electrical‐device therapy for patients with heart failure with reduced ejection fraction (HFrEF). Patients with left ventricular ejection frac...